Poncet's disease diagnostic criteria decodes conundrum: Poncet's vs pseudo Poncet's - V. Shobha; A.M. Desai (PAGEPress Publications, 2019)
Poncet's disease is very important and yet a challenging diagnosis of importance in countries with high TB endemicity (e.g. India). In this case series, we present 5 patients with diagnosed as Poncet's disease and in our tertiary health care center over 12 months and examine the performance of the diagnostic criteria suggested by Sharma and Pinto. The majority (4/5) of the patients were subsequently diagnosed and responded to anti-tuberculous therapy. In the other patient, a diagnosis of atypical seropositive rheumatoid arthritis or Pseudo Poncet's disease was established on follow up.